Factors Associated with the Occurrence of Contact Dermatitis at PT IMIP in Morowali Regency - Baeda, Abd. Gani; Siagian, Heriviyatno; Bansoe, Dessy Krishna; Yulianti, Sri; Anam, Akhyarul (International Journal of Nursing and Health Services (IJNHS), 2022)
Background: Skin disease due to work is the second most common disease after musculoskeletal disease, accounting for 22% of all occupational diseases. Objective: The purpose of this research was to determine the factors associated with the incidence of contact dermatitis at PT IMIP in Morowali Regency. Method: This type of research is analytic research with a case control approach. The sample was the total population. Result: The results of the research were analyzed using univariate and bivariate analysis. The results show that of 100 respondents, both the case and the control group that have good personal hygiene amounted to 65.0%, respondents who have no allergic history amounted to 89.0%, contact duration ? 2 years amounted to 62.0%,use personal protective equipment amounted to 65.0% incidence of contact dermatitis respectively 50%. Chi-Square test results of personal hygiene, allergic history, contact duration and the use of personal protective equipment obtained p value= 0.000 and p value= 0,007 (£0.05). This means that statistically, there is a significant relationship between personal hygiene, allergic history, contact duration and the use of personal protective equipment with the occurrence of contact dermatitis. Recommendation: suggestions for PT IMIP in Morowali Regency to further enhance socialization to employees about the importance of maintaining health, especially in preventing skin diseases including contact dermatitis and motivate the employees in order to civilize the use of personal protective equipment when working